Audit Sistem Manajemen Inventori Berbasis Web Untuk Usaha Kecil Dan Menengah - Witriana, Witriana (Jurnal Pengembangan Sistem Informasi dan Informatika, 2025)
Inventory recording is very important for business actors, not only for large companies but also for Micro, Small and Medium Enterprises (MSMEs). Inventory Management System Audit is an evaluation process. Comprehensive recording of incoming and outgoing goods can reduce errors, streamline work processes, and make subsequent investment decisions easier. However, due to limited human resources in the field of information technology, MSMEs sometimes still record manually. RUMAH CANTIK JIHAN Store, which is an MSME that provides various kinds of household appliances, also experiences this problem. Business owners need help to monitor the turnover of incoming and outgoing goods transactions. The purpose of this study is to provide convenience in the process of incoming and outgoing goods transactions, facilitate the processing of incoming and outgoing goods transaction data, minimize errors in recording transaction data. The purpose of this study resulted in several uses consisting of using the approach method used is a descriptive qualitative approach. The analysis tools used are Use case Diagram, Class Diagram, Activity Diagram. The method used in this study is the System Development Life Cycle (SDLC), because each process is clearly defined and easy to understand. The results of the study showed that this system functions well, speeds up employees in recording transactions of incoming and outgoing goods, and makes it easier for owners to monitor business activities and allocate funds appropriately for the procurement of new goods.